Harnessing the impact of biodegradable materials for sustainable concrete innovations, enhanced mechanical and corrosion mitigation A Mini review - Fayomi, Ojo S. I. (Edelweiss Applied Science and Technology, 2025)
This mini review explores the use of agricultural waste as supplementary cementitious materials (SCMs) to address environmental and performance challenges in the construction industry. The study employs a secondary data approach through a literature review for a comprehensive overview. Agricultural residues such as rice husk ash, sugarcane bagasse ash, and coconut shell ash possess pozzolanic properties that enhance the mechanical and durability characteristics of concrete while reducing the consumption of conventional cement. These materials contribute to sustainability by decreasing carbon dioxide emissions during concrete production and addressing agro-waste management issues. Additionally, natural fibers like sugarcane bagasse fibers improve tensile strength, offer superior flexural properties, and exhibit excellent resistance to corrosion, making them suitable for structural applications. The review emphasizes the potential of agricultural wastes to reduce greenhouse gas emissions and conserve natural resources, while also discussing challenges and future research directions to optimize their utilization.